Comparative Ecological Perspectives of Two Ancient Lineages of Gray Wolves: Woolly Wolf (Canis lupus chanco) and Indian Wolf (Canis lupus pallipes) - Khan, Shaheer; Shrotriya, Shivam; Sadhukhan, Sougata; Lyngdoh, Salvador; Goyal, Surendra P.; Habib, Bilal (Frontiers in Ecology and Evolution, 2022)
Geographical isolation can often lead to speciation, and two disconnected populations of the same species living in drastically different bioclimatic regions provide an opportunity to understand the process of speciation. The Woolly wolf is found in the cold-arid, Trans-Himalayan landscape, while the Indian wolf inhabits the semi-arid grasslands of Central India. Both the lineages of wolves from India have generated scientific debate on their taxonomic status in recent years. In this study, we collected data and reviewed published literature to document the ecological and behavioral differences between the Woolly wolf and the Indian wolf. Most studies have used genetic data; hence we discuss variation in spatial ecology, habitat preferences, vocalization, diet diversity and cranial measurements of these two subspecies. The spatial ecology of two lineages was compared from the data on three Woolly and ten Indian wolves tagged with GPS collars. The telemetry data shows that there has been no difference in the day-night movement of Woolly wolves, whereas Indian wolves show significant high displacement during the night. The BBMM method indicated that Woolly wolf home ranges were three times larger than the Indian wolf. The Woolly wolf diet is comprised of 20 different types of food items, whereas the Indian wolf diet consists of 17 types. The Woolly and Indian wolf largely depend upon domestic prey base, i.e., 49.32 and 40.34%, respectively. We found no differences in the howling parameters of these subspecies. Moreover, the Woolly wolf skull was significantly longer and broader than the Indian wolf. Wolves of India are ancient and diverged from the main clade about 200,000-1,000,000 years ago. Their genetic and ecological evolution in different bioclimatic zones has resulted in considerable differences as distinct subspecies. The present study is a step in understanding ecological differences between two important, genetically unique subspecies of wolves.